Desmetramadol Is Identified as a G-Protein Biased µ Opioid Receptor Agonist - Zebala, John A.; Schuler, Aaron D.; Kahn, Stuart J.; Maeda, Dean Y. (Frontiers in Pharmacology, 2020)
Tramadol is widely used globally and is the second most prescribed opioid in the United States. It treats moderate to severe pain but lethal opioid-induced respiratory depression is uncommon even in large overdose. It is unknown why tramadol spares respiration. Here we show its active metabolite, desmetramadol, is as effective as morphine, oxycodone and fentanyl in eliciting G protein coupling at the human µ opioid receptor (MOR), but surprisingly, supratherapeutic concentrations spare human MOR-mediated βarrestin2 recruitment thought to mediate lethal opioid-induced respiratory depression.